2017
DOI: 10.1155/2017/8629234
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Stem Cell Markers Drive Progression, Therapeutic Resistance, and Bone Metastasis

Abstract: Metastatic or recurrent tumors are the primary cause of cancer-related death. For prostate cancer, patients diagnosed with local disease have a 99% 5-year survival rate; however, this 5-year survival rate drops to 28% in patients with metastatic disease. This dramatic decline in survival has driven interest in discovering new markers able to identify tumors likely to recur and in developing new methods to prevent metastases from occurring. Biomarker discovery for aggressive tumor cells includes attempts to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 100 publications
0
98
0
Order By: Relevance
“…In our study, we utilized the markers CXCR4 and CD117 to examine the numbers of circulating progenitor cells in the bloodstream. These two receptors are classic markers of cells residing in the bone marrow but are also postulated to be expressed on circulating tumor cells [30,46]. Using a syngeneic model, we are unable to determine the origin of these cells definitively, but their numbers are indicative of pre-metastatic niche formation and progression of cancers toward a more aggressive phenotype which is being driven by platelet-sequestered proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we utilized the markers CXCR4 and CD117 to examine the numbers of circulating progenitor cells in the bloodstream. These two receptors are classic markers of cells residing in the bone marrow but are also postulated to be expressed on circulating tumor cells [30,46]. Using a syngeneic model, we are unable to determine the origin of these cells definitively, but their numbers are indicative of pre-metastatic niche formation and progression of cancers toward a more aggressive phenotype which is being driven by platelet-sequestered proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[11]- [18] Several markers for CTCs and CSCs are postulated in the literature. [7] In a prior study, we identified CD117/c-kit positive CTCs in prostate cancer patients that were associated with cancer severity and biochemical recurrence. [19] CD117+ cell numbers were increased in the prostate tissue and circulation of patients with Gleason 8+ disease.…”
Section: Introductionmentioning
confidence: 96%
“…[3], [5], [6] However, <0.01% of these cells will initiate metastases. [3], [5] While multiple markers were proposed for prostate cancer CTCs, [7] most have yet to be validated in the circulation of patients. Further, it remains unproven whether CTCs can initiate metastases, which is partially due to an inability to examine the journey of CTCs from the primary tumor to the metastatic niche.…”
Section: Introductionmentioning
confidence: 99%
“…being a bona fide CSC marker for prostate and pancreatic cancers [44,45], evidently support its presence to promote therapy resistance. Also, studies in AML and NSCLC showed the presence of CXCR4 has a positive correlation with therapy resistance though they consider ligand-mediated signals as a responsible reason for the same [46,47].…”
Section: Discussionmentioning
confidence: 79%